Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.ppat.1006930
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and protein damage responses mediate artemisinin resistance in malaria parasites

Abstract: Due to their remarkable parasitocidal activity, artemisinins represent the key components of first-line therapies against Plasmodium falciparum malaria. However, the decline in efficacy of artemisinin-based drugs jeopardizes global efforts to control and ultimately eradicate the disease. To better understand the resistance phenotype, artemisinin-resistant parasite lines were derived from two clones of the 3D7 strain of P. falciparum using a selection regimen that mimics how parasites interact with the drug wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
184
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(198 citation statements)
references
References 100 publications
(187 reference statements)
13
184
0
1
Order By: Relevance
“…Resistance to artemisinin has long been thought to be multigenic, consistent with our model presented above 14,53 . So far, laboratory evolution of artemisinin resistance has mostly generated parasites with K13 mutations that are different from those most prevalent in the field, or mutations in other loci altogether, such as the recently-described pfcoronin 6,14,47 . Similarly, the AP-2µ(I592T) mutation described in this study has not been observed in human infections.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to artemisinin has long been thought to be multigenic, consistent with our model presented above 14,53 . So far, laboratory evolution of artemisinin resistance has mostly generated parasites with K13 mutations that are different from those most prevalent in the field, or mutations in other loci altogether, such as the recently-described pfcoronin 6,14,47 . Similarly, the AP-2µ(I592T) mutation described in this study has not been observed in human infections.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of the parasites are primed for stress adaptation under normal conditions. Stress responsiveness is an important determinant for drug resistance in P. falciparum [14,15]. This is also evident from the fact that even a clonal population of resistant parasites do not show complete resistance (varying Ring Survival Assay (RSA) levels, a measure of resistance against artemisinin [44].…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the fact that during heat stress there is an increase in virulence (var) gene expression which helps in the binding of infected RBCs to the endothelial receptors resulting in cytoadherence [12]. Recent reports also suggest stress responses as crucial mediator of artemisinin resistance in P. falciparum [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A further 65 genes were significantly enriched in individual screens ( Supplementary Table 4). Because K13 resistance alleles retain function and have not been recovered by selection in culture, the absence of K13 from our loss-of-function screens was expected 12,13,17,18,20,21 .…”
Section: Genome-wide Screens Implicate Tca and Heme Biosynthesis Pathmentioning
confidence: 99%
“…The mechanism underlying this effect remains under scrutiny, but it is thought to involve changes in the unfolded protein response, autophagy, and PI3K activity [14][15][16][17] . Decreased ART sensitivity has also been attributed to mutations unrelated to K13, such as coronin 18 , clathrin adaptors [19][20][21] , and cysteine proteases 22 . P. falciparum strains without identified causative mutations have displayed decreased clearance as well 23,24 .…”
Section: Introductionmentioning
confidence: 99%